Enhanced optical properties of chitosan polymer doped with orange peel dye investigated via UV–Vis and FTIR analysis - Dyari M. Mamand; Dana S. Muhammad; Shujahadeen B. Aziz; Peshawa O. Hama; Bandar A. Al-Asbahi; Abdullah A. A. Ahmed; Jamal Hassan (Scientific Reports)
Abstract The current research aims to determine the impact of orange peel dye (OPD), an eco-friendly addition, on the optical properties of biodegradable polymers. This study investigates the enhancement of optical properties in solid electrolytes based on chitosan (CS) and glycerol, with varying OPD concentrations. UV–Vis-NIR spectroscopy revealed significantly enhanced UV–visible light absorption in the 200–500 nm region and effective UV light blocking. FTIR analysis showed strong interactions between OPDs and the CS matrix, with functional groups such as O–H, C=O, and C=C. UV–Visible spectroscopy indicated a reduction in the optical band gap from 5.11 eV in pure CS to 2.93 eV and 2.84 eV with increasing OPD concentrations, reflecting alterations in the electronic structure and enhanced sub-bandgap states. The refractive index improved from 1.31 in pure CS to 1.54 and 1.62 in the doped electrolytes, attributed to increased optical density and light-harvesting capability. Optical basicity also increased from 1.01 to 1.32, enhancing donor properties. These results suggest that OPD-doped CS solid electrolytes offer enhanced optical properties, making them suitable for optoelectronic and UV-blocking applications due to their tunable band gap, improved polarizability, and enhanced light interaction.